2020
DOI: 10.1371/journal.pone.0230798
|View full text |Cite
|
Sign up to set email alerts
|

Applying univariate vs. multivariate statistics to investigate therapeutic efficacy in (pre)clinical trials: A Monte Carlo simulation study on the example of a controlled preclinical neurotrauma trial

Abstract: Background Small sample sizes combined with multiple correlated endpoints pose a major challenge in the statistical analysis of preclinical neurotrauma studies. The standard approach of applying univariate tests on individual response variables has the advantage of simplicity of interpretation, but it fails to account for the covariance/correlation in the data. In contrast, multivariate statistical techniques might more adequately capture the multi-dimensional pathophysiological pattern of neurotrauma and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Additionally, 3’UTR distribution bias was observed in the Clontech library preparation as previously reported in poly(A) based strategies [ 3 ]. Using principal component analysis (PCA) [ 36 ], we observed that all samples clustered according to their isolation technique and library preparation strategy ( Supplementary Materials Figure S4C ). To avoid 3’UTR distribution bias and since we were using low-input material isolated from the selected neuronal populations, we decided to use the Nugen Ovation Solo as our library preparation strategy for the following transcriptional analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 3’UTR distribution bias was observed in the Clontech library preparation as previously reported in poly(A) based strategies [ 3 ]. Using principal component analysis (PCA) [ 36 ], we observed that all samples clustered according to their isolation technique and library preparation strategy ( Supplementary Materials Figure S4C ). To avoid 3’UTR distribution bias and since we were using low-input material isolated from the selected neuronal populations, we decided to use the Nugen Ovation Solo as our library preparation strategy for the following transcriptional analyses.…”
Section: Resultsmentioning
confidence: 99%
“…First, the study’s sample size is relatively small. As considering more than one variable increases sensitivity in multivariate analyses, our approach with multivariate cross-correlation has benefits in overcoming small sample sizes with a high amount of features as well as detecting treatment effects with longitudinal data 55 . Second, although the primary goal was to evaluate the predictive capacity of imaging rather than to determine the factors contributing to clinical outcomes, measures of lesion topography shall be included in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The literature concerning time-series forecasting has to a heterogeneous and dynamic degree taken into account an extensive amount of scientific production and competitions for evaluating models applied to observed data in different fields of knowledge [19][20][21]. It is possible to find in the literature prediction comparisons in which univariate time-series models are superior to (or as good as) multivariate models (as in the discussion proposed in [22][23][24][25]). A possible interpretation for this result is a sparse representation, in large-scale models, of the dynamic interactions in a system of variables [26].…”
Section: Introductionmentioning
confidence: 99%